Transition of Islamic banks from debt-based modes to equity-based financing: issues and prospects - Sadique, Muhammad Abdurrahman (2010)
Equity financing seeks to achieve mutual sharing of risks pertaining to the enterprise and an equitable distribution of the return. Application of equity financing modes in Islamic banking is seen to be less developed, and configured in a manner that downplays their true potential. Some equity modes in vogue embody aspects more reflective of debt financing. Continued operation of these modes could not be expected to realise the fruits of Islamic economic ideals. To promote equity modes, some restriction should be introduced on the proliferation of debt-based schemes in areas of financing. Equity modes currently utilised could be further upgraded to ensure sharī‛ah compliance while realising their socioeconomic objectives. The aspect of existence and availability of capital at the formation of equity partnership should be reassessed, as considerable emphasis has been placed on it in shari‘ah. The mechanism employed by Islamic banks in deciding the ratio of profit sharing may require further refinement. Adopting an equity format could solve problems faced in debt-based project financing from an Islamic perspective, in addition to realising justice and fair play.